2017
DOI: 10.1007/s00384-017-2756-1
|View full text |Cite
|
Sign up to set email alerts
|

Sigmoid resection for diverticulitis is more difficult than for malignancies

Abstract: The outcomes of our study show that diverticulitis may not be the ideal condition to start the learning process for laparoscopic colorectal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Kubat et al [ 20 ] described the same progression in robotic single-site cholecystectomies, who suggested that the learning curve could be accelerated by first acquiring the skills necessary to complete elective cases. This concept is not new when considering the studies by Stam et al [ 45 ] and Naguib et al [ 46 ] who highlighted that laparoscopic colorectal resections for diverticular disease are technically challenging and more difficult than the resections performed for oncological indications in an elective setting. The study by Miskovic et al, based on an international multicenter analysis of 4852 cases, confirmed that the learning curve in colorectal surgery should include difficult cases like emergency surgery only in the later stages [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Kubat et al [ 20 ] described the same progression in robotic single-site cholecystectomies, who suggested that the learning curve could be accelerated by first acquiring the skills necessary to complete elective cases. This concept is not new when considering the studies by Stam et al [ 45 ] and Naguib et al [ 46 ] who highlighted that laparoscopic colorectal resections for diverticular disease are technically challenging and more difficult than the resections performed for oncological indications in an elective setting. The study by Miskovic et al, based on an international multicenter analysis of 4852 cases, confirmed that the learning curve in colorectal surgery should include difficult cases like emergency surgery only in the later stages [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The learning curve in laparoscopic right hemicolectomy in the emergency setting is steeper compared to the elective one, primarily due to the local inflammation that subverts the normal anatomy 22 : Surgery should be performed by expert hands to improve surgical outcomes, reducing operative time, the LOS, and ensuring the best possible assistance to the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various statistical methodologies that have been employed for the LC evaluation are the group splitting, moving average, and CUSUM analysis[ 3 , 17 , 32 , 33 ]. Following an introductory learning phase, the trainee is gradually performing operations of higher complexity and difficulty[ 34 , 35 ]. Finally, once the iteration of the process does not affect the measured variable, mastery is achieved[ 16 , 17 , 32 ].…”
Section: Discussionmentioning
confidence: 99%